Multispecies study: Low dose tributyltin impairs ovarian theca cell cholesterol homeostasis through the RXR pathway in five mammalian species, including humans. - Pu, Yong (Arch Toxicol, 2019)
Tributyltin (TBT), an organotin chemical used as a catalyst and biocide, can stimulate cholesterol efflux in non-steroidogenic cells. Since cholesterol is the first limiting step for sex hormone production, we hypothesized that TBT disrupts intracellular cholesterol transport and impairs steroidogenesis in ovarian theca cells. We investigated TBT’s effect on cholesterol trafficking, luteinization, and steroidogenesis in theca cells of five species (human, sheep, cow, pig, and mice). Primary theca cells were exposed to an environmentally relevant dose of TBT (1 or 10 ng/ml) and/or retinoid X receptor (RXR) antagonist. The expression of RXRα in sheep theca cells was knocked down by using shRNA. Steroidogenic enzymes, cholesterol transport factors, and nuclear receptors were measured by RT-qPCR and western blotting, and intracellular cholesterol, progesterone, and testosterone secretion by ELISA. In ovine cells, TBT upregulated StAR, ABCA1, and SREBF1 mRNA in theca cells. TBT also reduced intracellular cholesterol and upregulated ABCA1 protein expression but did not alter testosterone or progesterone production. RXR antagonist and RXRα knockdown demonstrates that TBT’s effect is partially through RXR. TBT’s effect on ABCA1 and StAR expression was recapitulated in all five species. TBT, at an environmentally relevant dose, stimulates theca cell cholesterol extracellular efflux via the RXR pathway, triggers a compensatory upregulation of StAR that regulates cholesterol transfer into the mitochondria and SREBF for de novo cholesterol synthesis. Similar results were obtained in all five species evaluated (human, sheep, cow, pig, and mice) and are supportive of TBT’s conserved mechanism of action across mammalian species.